PENGUKURAN INFILTRASI TANAH BUKIT PINANG-PINANG KAWASAN HUTAN HUJAN TROPIK GUNUNG GADUT PADANG DI LABORATORIUM - Yulnafatmawita Yulnafatmawita; Asmar Asmar; Ricci Enrella (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2009)
A research about infiltration rate of soils from Pinang-Pinang area, a super wet tropical rain forest gunung Gadut Padang, was conducted in soil laboratory Agriculture Faculty, Andalas University. Pinang-pinang area is located in Kecamatan Pauh, in the upper footslope of Gadut mountain, functiong as water regulation for the area down under, especially Padang city. This is caused by the fact that water from the Pinang-Pinang area will fow to the sea through Kuranji river. This area is supposed to be protected to avoid natural disaster in the area down under. This research was aimed to determine infiltration rate of soils under different land use in the Pinang-Pinang region. There were three land use in this area, forest, mixed garden, and bush. Undisturbed soil samples were taken from each land use by using 11-cm in diameter and 40 cm height tubes. Soils samples were tightly closed, and brought into laboratory. Infiltration rate from each soil samples were determined in laboratory. The results showed that mixed garden gave the highest infiltration rate (38.4 cm jam-1) among the land use tested, and then followed by forest land use, and then bush land.Key Words: infiltration, land use, tropical rain forest